Representations of Feminism in Linda Howard’s Cry No More: A Sara Mills Feminist Stylistics Analysis - Chairani, Sri; Manugeren, M; Arafah, Burhanuddin; Purwarno, Purwarno (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2025)
This study examines the representation of feminism in Linda Howard’s novel Cry No More using Sara Mills’ Feminist Stylistics model. Situated within the romance thriller genre, the novel offers a productive site to explore how female agency is negotiated between empowerment and vulnerability. The data consist of selected narrative units featuring the protagonist, Milla Edge, which are analyzed through lexical and syntactic categorization focusing on Subject–Object positioning and reader positioning. The analysis reveals three dominant patterns: Milla is constructed as an active Subject through high-transitivity verbs and agentic nominalizations in her role as leader of the “Finders” organization; she is simultaneously rendered an Object via passive structures and a lexicon of suffering; and key resolutions of the plot often depend on male protectors. These findings demonstrate that Milla’s agency functions as “negotiated empowerment,” thereby contributing to feminist Critical Discourse Analysis of popular fiction by showing how patriarchal norms are both challenged and reproduced at the level of linguistic choice.